An experimental investigation of a low temperature Al2O3-H2O nanofluid based direct absorption solar collector. (August 2015) - Gupta, Hemant Kumar; Agrawal, Ghanshyam Das; Mathur, Jyotirmay
Highlights: A direct absorption solar collector (area 1.4 m 2 ) with glass base plate is designed and tested. Outdoor experiments are performed using nanofluid and water to analyze the efficiency of the collector. DASC Collector with nanofluid is more efficient than water. Efficiency enhancement is the highest up to 0.005% volume fraction of Al2 O3 nanoparticles. Evaluated the effect of volume fraction of Al2 O3 nanoparticles and nanofluid flow rate. Abstract: The conventional tube-in-plate type flat plate solar collectors have low efficiency and higher heat losses due to surface based solar energy absorption and indirect transfer of heat from hot absorber surface to working fluid flowing through tubes. A full scale direct absorption solar collector having gross area of 1.4 m 2 and working on volumetric absorption principle was developed to perform experimental study using thin film of Al2 O3 -H2 O nanofluid. Use of nanofluid as working fluid improves the optical and thermo physical properties that result into an increase in the efficiency of the collector. Experimentation was carried using four different volume fractions of 20 nm Al2 O3 nanoparticles, 0.001%, 0.005%, 0.01% and 0.05%. ASHRAE standard 93-86 was followed for calculation of instantaneous efficiency of solar collector. Improvement in efficiency of solar collector has been recorded in all four cases of using nanofluids in place of water. Instantaneous efficiency enhancement of 22.1%, 39.6%, 24.6% and 18.75% has been observed for 0.001%, 0.005%, 0.01% and 0.05% volume fraction respectively. The experimental results also indicated that collector efficiency peaked at certain volume fraction, and decreased for lower and higher values of volume fraction.